The national health system’s structural shortfalls, between history and actuality: interrogatives on the implementation of proximity-care reformation (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Having examined the constitutional foundation of health protection and reaffirmed its historical and political nature, the article aims to propose several lines of analysis regarding the implementation of the proximity care reformations, as framed in the mission Health of the National Recovery and Resilience Plan, by contextualizing it within the National Health System’s transformative crisis and its historical and structural shortfalls.
Keywords: Proximity healthcare reformation; right to health; constitutional principles; pandemic; public health